The story of Andrew Jackson - Meadowcroft, Enid La Monte 1898- (Signature books, 1953)
A biography of the President who wasted his inheritance on horse racing and cock fights, fatally wounded a lawyer in a pistol duel, and married a divorcaee in 1791.